2012
DOI: 10.1007/s12576-011-0189-0
|View full text |Cite
|
Sign up to set email alerts
|

ACE I/D, ACTN3 R577X, PPARD T294C and PPARGC1A Gly482Ser polymorphisms and physical fitness in Taiwanese late adolescent girls

Abstract: Physical performance of youth is influenced by various factors, including body composition, biological maturity status, level of habitual physical activity, and muscular strength. Muscular strength has been largely attributed to genetic effects. To exclude possible confounding effects from various acquired factors, this study examined the relationships between polymorphisms of the angiotensin-converting enzyme (ACE), α-actinin-3 (ACTN3), peroxisome proliferator-activated receptor delta (PPARD), and peroxisome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
0
21
0
3
Order By: Relevance
“…The R allele was also associated with better 40m sprint performance in adolescent Greek boys (35). Late adolescent girls with the RR genotype performed better on sit up tests than girls with the RX genotype (32). However, the ACTN3 genotype was not associated with several other power or endurance phenotypes in adolescents of either sex (35).…”
Section: Relevance For Young Athletesmentioning
confidence: 88%
See 1 more Smart Citation
“…The R allele was also associated with better 40m sprint performance in adolescent Greek boys (35). Late adolescent girls with the RR genotype performed better on sit up tests than girls with the RX genotype (32). However, the ACTN3 genotype was not associated with several other power or endurance phenotypes in adolescents of either sex (35).…”
Section: Relevance For Young Athletesmentioning
confidence: 88%
“…The ACE II polymorphism was reported to be associated with significantly greater handgrip strength and vertical jump performance in female, but not male Greek adolescents (31), which contrasts the typical association of the D allele with better strength and power in adults. Recently, the ACE D allele has been associated with greater handgrip strength in adolescent girls (32) and standing long jump performance in middle-school age children (33). …”
Section: Relevance For Young Athletesmentioning
confidence: 99%
“…Yang for the first time reported that none of the Olympians or female power athletes had the XX genotype [16]. Taiwanese late adolescent girls with the ACTN3 RR genotype performed significantly better in terms of handgrip strength than those with other genotype combinations [22]. Women with the ACTN3 XX genotype have weaker lower body strength than those with the RX genotype [2324].…”
Section: Discussionmentioning
confidence: 99%
“…En el campo de la genética, las investigaciones se han orientado en la búsquedas de perfiles genéticos asociados al rendimiento deportivo de atletas de elite que permitan la orientación del entrenamiento y selección deportiva (Alfred et al, 2011). Dos genes han sido ampliamente estudiados y asociados al rendimiento deportivo, la enzima convertidora de angiotensina inserción/deleción (ECA I/D) polimorfismo y el gen de la a-actina-3 (ACTN3) polimorfismo R577X (Ahmetov et al, 2013;Alfred et al;Chiu et al, 2012; Doring et al, 2010).…”
Section: Introductionunclassified
“…En el campo de la genética, las investigaciones se han orientado en la búsquedas de perfiles genéticos asociados al rendimiento deportivo de atletas de elite que permitan la orientación del entrenamiento y selección deportiva (Alfred et al, 2011). Dos genes han sido ampliamente estudiados y asociados al rendimiento deportivo, la enzima convertidora de angiotensina inserción/deleción (ECA I/D) polimorfismo y el gen de la a-actina-3 (ACTN3) polimorfismo R577X (Ahmetov et al, 2013;Alfred et al;Chiu et al, 2012; Doring et al, 2010).La ECA, localizado en el cromosoma 17, implicada en el sistema renina angiotensina aldosterona actúa en la regulación del volumen sanguíneo, presión arterial y balance de electrolitos (McCauley et al, 2010). La inserción (I) y deleción (D) como polimorfismo, se ha asociado con mejoras en el rendimiento deportivo otorgando al alelo I de la ECA una asociación con el rendimiento en pruebas de resistencia y al alelo D un mejor desempeño en pruebas de fuerza y velocidad (McCauley et al;Rodriguez-Romo et al, 2010).…”
unclassified